2015
DOI: 10.1007/s00380-015-0681-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise-based cardiac rehabilitation on non-culprit mild coronary plaques in the culprit coronary artery of patients with acute coronary syndrome

Abstract: Approximately, 70 % of acute myocardial infarctions are known to develop from mild atherosclerotic lesions. Therefore, it is important to evaluate mild coronary plaques to prevent acute coronary syndrome (ACS). The aim of the present study was to investigate the effects of exercise-based cardiac rehabilitation (CR) on mild coronary atherosclerosis in non-culprit lesions in patients with ACS. Forty-one men with ACS who underwent emergency percutaneous coronary interventions and completed a 6-month follow-up wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
0
8
0
3
Order By: Relevance
“…Cardiac rehabilitation (CR) aims at restoring exercise performance [1] in patients after a cardiac event like myocardial infarction (MI) [1], peripheral arterial disease [2,3] or heart failure (HF). [3][4][5][6][7] CR uses multifactorial intervention, including aggressive risk factor modification [8][9][10][11]7].…”
Section: B Introductionmentioning
confidence: 99%
“…Cardiac rehabilitation (CR) aims at restoring exercise performance [1] in patients after a cardiac event like myocardial infarction (MI) [1], peripheral arterial disease [2,3] or heart failure (HF). [3][4][5][6][7] CR uses multifactorial intervention, including aggressive risk factor modification [8][9][10][11]7].…”
Section: B Introductionmentioning
confidence: 99%
“…There was also a significant improvement of exercise capacity after CR in both examined groups. Previously published studies have shown that CR programs based on regular physical activity improve exercise capacity and ability to perform physical exercise in patients with CAD, [21][22][23]32 and also in CAD patients with type-2 diabetes. 24 The analysis of HRV indices have shown that after 8 weeks of CR SDNN and pNN50% in time domain and TP and HF component in frequency domain were significantly higher than before CR in the CAD patients without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory markers-such as C-reactive protein level, interleukin-6 level, and proinflammatory cytokine-are major factors that influence the development of ACS [20,21]. Kurose et al reported a decrease in high sensitive C-reactive protein as an independent predictor of coronary plaque regression in ASC patients who participated in CR [22]. We reported that CR for 6 months ameliorated not only metabolic parameters, but also the exercise capacity, muscle strength, and inflammatory state in metabolic syndrome patients after CABG [23].…”
Section: Discussionmentioning
confidence: 99%